2016
DOI: 10.1088/0264-9381/33/12/125026
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetric backgrounds and generalised special holonomy

Abstract: We define intrinsic torsion in generalised geometry and use it to introduce a new notion of generalised special holonomy. We then consider generic warped supersymmetric flux compactifications of M theory and Type II of the form R D−1,1 × M . Using the language of E d(d) ×R + generalised geometry, we show that, for D ≥ 4, preserving minimal supersymmetry is equivalent to the manifold M having generalised special holonomy and list the relevant holonomy groups. We conjecture that this result extends to background… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
191
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(191 citation statements)
references
References 159 publications
(483 reference statements)
0
191
0
Order By: Relevance
“…In [17], it was shown that the left-hand side of (2.16) matches exactly the intrinsic torsion T int of the generalised G-structure 3 as listed in table 1. The right-hand side, which simply vanished in the Minkowski case, now contains just the cosmological constant multiplying the (G-invariant) Killing spinor.…”
Section: Generalised Structures With Singlet Torsionmentioning
confidence: 75%
See 4 more Smart Citations
“…In [17], it was shown that the left-hand side of (2.16) matches exactly the intrinsic torsion T int of the generalised G-structure 3 as listed in table 1. The right-hand side, which simply vanished in the Minkowski case, now contains just the cosmological constant multiplying the (G-invariant) Killing spinor.…”
Section: Generalised Structures With Singlet Torsionmentioning
confidence: 75%
“…It was further claimed in [17] that generic minimally supersymmetric AdS compactifications could be similarly described, now by keeping certain singlet components of the generalised intrinsic torsion as a non-zero constant, corresponding to the cosmological constant Λ. We thus have that In the following we will clarify this statement and demonstrate it explicitly.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations